SANTOS, G. G. dos; SAMPAIO, S. M. R; CARVALHO, A. Observatório da vida estudantil: avaliação e qualidade no ensino superior: formar como e para que mundo? Salvador: Edufba, 2015. 342 p. - Resende, Franciele Daiane Rodrigues (Caderno CRH, 2017)
http://dx.doi.org/10.1590/S0103-49792016000200013